Method for producing polysulfone hollow fiber membrane

JP7636241B2Active Publication Date: 2025-02-26NOK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021064676
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-06
Publication Date
2025-02-26
Estimated Expiration
2041-04-06

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、中空糸膜の浸漬処理を施しても、優れた分離性能と透水性能の両立が可能なポリスルホン中空糸膜の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636241000002
    Figure 0007636241000002
  • Figure 0007636241000001
    Figure 0007636241000001
Patent Text Reader

Abstract

To provide a manufacturing method of a polysulfone hollow fiber membrane capable of achieving coexistence of separation performance and permeability performance, even if an immersion treatment of the hollow fiber membrane is applied.SOLUTION: In a manufacturing method of a polysulfone hollow fiber membrane, after producing a hollow fiber membrane by dry wet spinning by discharging from a double ring nozzle, together with core liquid, spinning dope containing 10 mass% or more and 40 mass% or less polysulfone, 1 mass% or more and 30 mass% or less polyvinyl pyrrolidone, and 1 mass% or more and 80 mass% or less water-soluble organic solvent, the hollow fiber membrane is immersed into compressed water at 120°C or higher and 130°C or lower at least for two hours.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polysulfone hollow fiber membrane. [Background technology]

[0002] Filtration techniques using porous membranes such as microfiltration membranes and ultrafiltration membranes have been put to practical use in many fields, such as the pharmaceutical field, the water purification field, sterilization in the food industry, and ultrapure water production in the semiconductor industry. For example, porous membranes used in the water purification field are used not only for sterilization of drinking water, but also for sterilization and turbidity removal in the sewage field. In particular, porous membranes made of polysulfones are widely used for sterilization in the water purification field.

[0003] The sterilization and permeability performance required for porous membranes in the water purification field is greatly affected by the pore size on the surface of the porous membrane. For example, in a porous membrane, if the pore size is small, the sterilization performance, i.e., separation performance, increases, but the permeability performance (water permeability) decreases, creating a trade-off relationship.

[0004] In order to achieve both separation performance and water permeability, a technique for controlling the structure of the inner surface of a porous hollow fiber membrane is known. Patent Document 1 discloses that the minor and major diameters of the pores on the surface of the hollow fiber membrane are controlled within a desired range to achieve both virus removal performance and water permeability.

[0005] On the other hand, when producing a hydrophilic hollow fiber membrane from hydrophobic polysulfone, it is known that hydrophilicity is imparted by mixing with a hydrophilic polymer such as polyvinylpyrrolidone. It is desirable that the polysulfone hollow fiber membrane to which hydrophilicity has been imparted can maintain its hydrophilicity for as long as possible.

[0006] Patent Document 2 discloses a method of dry-wet spinning a hollow fiber membrane from a polysulfone spinning solution containing a predetermined amount of polyvinylpyrrolidone, and then heating the resulting hollow fiber membrane in pressurized water at about 110°C or higher for 15 to 60 minutes and washing the membrane to impart permanent hydrophilicity to the polysulfone hollow fiber membrane.

[0007] Although Patent Document 1 discloses the virus removal performance and water permeability of the hollow fiber membrane, it does not mention these performances after the hollow fiber membrane is immersed under certain washing conditions. That is, when the hollow fiber membrane is immersed as described in Patent Document 2 to impart permanent hydrophilicity to the hollow fiber membrane, there is a concern that the characteristics of the polysulfone hollow fiber membrane may be significantly affected depending on the washing conditions of the hollow fiber membrane. Therefore, it is necessary to carefully examine the effects of the washing conditions of the polysulfone hollow fiber membrane on the separation performance and water permeability. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2014-073487 A [Patent Document 2] Japanese Patent Application Publication No. 7-155573 Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention provides a method for producing a polysulfone hollow fiber membrane that is capable of achieving both excellent separation performance and water permeability even when the hollow fiber membrane is subjected to a immersion treatment. [Means for solving the problem]

[0010] In a method for producing a polysulfone hollow fiber membrane according to an embodiment of the present invention, a spinning dope containing 10% by mass or more and 40% by mass or less of polysulfone, 1% by mass or more and 30% by mass or less of polyvinylpyrrolidone, and 1% by mass or more and 80% by mass or less of a water-soluble organic solvent is discharged from a double ring nozzle together with a core liquid, a hollow fiber membrane is produced by dry-wet spinning, and the hollow fiber membrane is then immersed in pressurized water at 120° C. or more and 130° C. or less for at least 2 hours.

[0011] In one embodiment of the present invention, the core liquid contains 30% by mass or more and 100% by mass or less of N,N-dimethylformamide.

[0012] In one embodiment of the present invention, the water-soluble organic solvent comprises N,N-dimethylformamide.

[0013] In one embodiment of the present invention, the average pore size of the polysulfone hollow fiber membrane after immersion is 24 nm or more and 40 nm or less. Effect of the Invention

[0014] According to the present invention, there can be provided a method for producing a polysulfone hollow fiber membrane which is capable of achieving both excellent separation performance and water permeability even when the hollow fiber membrane is subjected to a immersion treatment. [Brief description of the drawings]

[0015] [Figure 1] 1A and 1B are schematic diagrams illustrating a method for measuring the water permeation rate (water permeability) of a hollow fiber membrane. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present embodiment will be described in detail below. In the method for producing a polysulfone hollow fiber membrane according to the present embodiment, a spinning dope containing a predetermined amount of polysulfone, polyvinylpyrrolidone, and a water-soluble organic solvent is discharged from a double ring nozzle together with a core liquid, and a hollow fiber membrane is produced by dry-wet spinning, and the obtained hollow fiber membrane is immersed in pressurized water at 120°C to 130°C for at least 2 hours. That is, by immersing the hollow fiber membrane obtained by dry-wet spinning in warm water within a predetermined temperature range for a predetermined time, the pore size of the hollow fiber membrane is adjusted to a few nanometers, and separation performance and water permeability are both achieved. In the conventional hollow fiber membrane immediately after spinning, the periphery of the polysulfone skeleton is coated with a hydrophilizing agent polymer (e.g., polyvinylpyrrolidone) like wax, so that it is presumed that if the hydrophilizing agent polymer is also coated on the pores of the hollow fiber membrane, the separation performance of the hollow fiber membrane is inhibited. In this embodiment, by controlling the conditions for immersion in hot water, the coating layer of the hydrophilizing agent polymer is dissolved in water, and the pore size of the hollow fiber membrane is slightly increased. As a result, even if the hollow fiber membrane is immersed in hot water, a polysulfone hollow fiber membrane that exhibits both excellent separation performance and water permeability can be produced.

[0017] As the polysulfone, commercially available products such as the Udel (registered trademark) series manufactured by Solvay Specialty Polymers and the Ultrason (registered trademark) S series manufactured by BASF can be used.

[0018] The content of polysulfone contained in the spinning dope is 10% by mass or more and 40% by mass or less, and preferably 12% by mass or more and 25% by mass or less. When the blending ratio of polysulfone is 10% by mass or more, the decrease in strength of the hollow fiber membrane during spinning is suppressed, and furthermore, the hollow fiber membrane is easily formed, and spinning can be performed more reliably. In addition, when the blending ratio of polysulfone is 40% by mass or less, holes are easily formed in the hollow fiber membrane, and therefore the decrease in water permeability can be suppressed.

[0019] The spinning dope containing polysulfone as a spinning (membrane-forming) component further contains polyvinylpyrrolidone and a water-soluble organic solvent.

[0020] Polyvinylpyrrolidone is added as a hydrophilic polymeric substance. The average molecular weight of polyvinylpyrrolidone is preferably 1000 to 1200000, more preferably 10000 to 120000. Examples of such polyvinylpyrrolidone include commercially available products such as "PVP K-30" manufactured by BASF. The content of polyvinylpyrrolidone contained in the spinning solution is 1% by mass to 30% by mass, and preferably 5% by mass to 20% by mass. By having the blending ratio of polyvinylpyrrolidone of 1% by mass or more, it is possible to impart sufficient hydrophilicity to the hollow fiber membrane, and further, it is possible to prevent the pore size of the hollow fiber membrane from becoming small, and to suppress the decrease in water permeability. In addition, by having the blending ratio of polyvinylpyrrolidone of 30% by mass or less, the spinning solution is stable, so that clouding is suppressed and spinning can be performed more reliably.

[0021] Examples of the water-soluble organic solvent include aprotic polar solvents such as methanol, ethanol, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone, or a mixture of two or more of these. Among these, N,N-dimethylformamide, which is the same as the main component of the core liquid described below, is preferred from the viewpoint of spinning stability. The content of the water-soluble organic solvent contained in the spinning dope is not particularly limited, but is preferably 1% by mass or more and 80% by mass or less, and more preferably 50% by mass or more and 75% by mass or more.

[0022] The spinning dope may further contain water as necessary, and the amount of water blended may be 1% by mass or less, preferably 0.3% by mass or more and 1% by mass or less.

[0023] The polysulfone hollow fiber membrane is produced by extruding the spinning dope containing the above-mentioned components together with the core liquid from a double ring nozzle and performing dry-wet spinning. In this case, the core liquid preferably contains 30% by mass or more and 100% by mass or less of N,N-dimethylformamide. When the core liquid is used as a solution, it is used as an aqueous solution further containing water. By using N,N-dimethylformamide with a concentration of 30% by mass or more and 100% by mass or less as the core liquid, it is possible to improve the water permeability of the polysulfone hollow fiber membrane. The extruding spinning dope is coagulated in a coagulation bath such as water, and then washed in a washing bath such as water.

[0024] The obtained hollow fiber membrane is subjected to an immersion treatment in which the hollow fiber membrane is immersed in pressurized water at 120°C to 130°C, preferably 120°C to 125°C, for at least 2 hours to wash the hollow fiber membrane. In this immersion treatment, the hollow fiber membrane is immersed in warm water for 2 hours or more under pressurized conditions using an autoclave or the like, and the hollow fiber membrane is simultaneously washed. By setting the heating temperature in the immersion treatment to within the range of 120°C to 130°C and the immersion time to at least 2 hours, it is possible to impart excellent separation performance and water permeability to the polysulfone hollow fiber membrane. The pressurization condition is preferably, for example, 0.2 MPa to 0.4 MPa.

[0025] The average pore size of the polysulfone hollow fiber membrane after the immersion treatment is preferably 24 nm or more and 40 nm or less, more preferably 24.5 nm or more and 30 nm or less. By having an average pore size of 24 nm or more, sufficient water permeability can be obtained, and by having an average pore size of 40 nm or less, the decrease in separation performance can be suppressed, and the polysulfone hollow fiber membrane can be given the desired sterilization performance. Such a polysulfone hollow fiber membrane having excellent separation performance and water permeability can be applied to, for example, a hollow fiber membrane module for a water purifier, and is particularly suitable for application as a virus removal membrane. EXAMPLES

[0026] Examples of the present invention will be described below, but the present invention is not limited to these examples as long as it does not deviate from the spirit of the present invention. In addition, unless otherwise specified, room temperature is within the range of 20°C ± 5°C.

[0027] Example 1 A spinning dope containing 19 mass % of polysulfone ("Ultrason (registered trademark) S3010" manufactured by BASF), 9 mass % of polyvinylpyrrolidone ("PVP K-30" manufactured by BASF), and 72 mass % of N,N-dimethylformamide was prepared at room temperature.

[0028] The obtained spinning solution was discharged from a double annular nozzle into a water coagulation bath by a dry-wet spinning method using a core liquid containing 60% by mass of N,N-dimethylformamide and 40% by mass of water to obtain a hollow fiber membrane. The obtained hollow fiber membrane was then immersed in pressurized water (0.21 MPa) at 121°C for 2 hours in an autoclave to produce a polysulfone hollow fiber membrane.

[0029] The prepared polysulfone hollow fiber membrane was subjected to the following measurements and evaluations, the results of which are shown in Table 1.

[0030] <Pore size measurement> The pore size of the polysulfone hollow fiber membrane was measured using a porometer ("Perm Porometer", manufactured by PMI Co., Ltd.), and the average pore size was calculated based on the half-dry principle. If the average pore size was 24 nm or more and 40 nm or less, the desired pore size was obtained, and the membrane was evaluated as having excellent separation performance.

[0031] <Measurement of permeability coefficient> The permeability coefficient of the polysulfone hollow fiber membrane was measured based on the amount of water permeated. Specifically, it was measured by the method shown in Figures 1A and 1B. A permeability coefficient of 7 or more was evaluated as excellent water permeability.

[0032] As shown in FIG. 1A, a cylindrical container 11 with a diameter of 8 mm, a length of 7.5 cm, and open ends was prepared. A 6 cm polysulfone hollow fiber membrane 13 was placed in the cylindrical container 11 in a U-shaped state. Next, the polysulfone hollow fiber membrane 13 was sealed and fixed to one end of the cylindrical container 11 using a potting agent 12 (epoxy resin; product name "Quick Set", manufactured by Konishi Co., Ltd.). The other end of the cylindrical container 11 was then sealed with a resin head 10.

[0033] Next, as shown in FIG. 1B, a tube 15 was provided so as to penetrate the resin head 10 and reach the inside of the cylindrical container 11. The tube 15 was branched into two, one of which was connected to a pressure gauge 14 and the other to a supply tube 16 for ion-exchanged water. After that, ion-exchanged water was supplied from the supply tube 16 into the cylindrical container 11 for one minute, and the inside of the cylindrical container 11 was pressurized until the pressure gauge reading reached 100 kPa. During this process, the volume of water 17 leaking out from the end of the cylindrical container 11 sealed with the potting agent 12 was measured. The amount of water 17 leaked out was then divided by the lateral surface area of ​​the polysulfone hollow fiber membrane 13 (diameter of the polysulfone hollow fiber membrane 13 × 3.14 × length of the polysulfone hollow fiber membrane 13) and time (1 / 60) to obtain the permeability coefficient (ml / (h cm 2 ) was calculated.

[0034] Example 2 A polysulfone hollow fiber membrane was produced in the same manner as in Example 1, except that the heating temperature in the immersion treatment was 125° C., and the above measurements and evaluations were carried out. The results are shown in Table 1.

[0035] Comparative Example 1 A polysulfone hollow fiber membrane was produced in the same manner as in Example 1, except that the heating temperature in the immersion treatment was 80° C., and the above measurements and evaluations were carried out. The results are shown in Table 1.

[0036] Comparative Example 2 A polysulfone hollow fiber membrane was produced in the same manner as in Example 1, except that the heating temperature in the immersion treatment was 100° C., and the above measurements and evaluations were carried out. The results are shown in Table 1.

[0037] Comparative Example 3 A polysulfone hollow fiber membrane was produced in the same manner as in Example 1, except that the immersion time in the immersion treatment was set to 1 hour, and the above measurements and evaluations were carried out. The results are shown in Table 1.

[0038] Comparative Example 4 A polysulfone hollow fiber membrane was produced in the same manner as in Example 1, except that the heating temperature in the immersion treatment was 135° C., and the above measurements and evaluations were carried out. The results are shown in Table 1.

[0039] [Table 1]

[0040] As shown in Table 1, a hollow fiber membrane produced using a spinning dope containing predetermined components was immersed in pressurized water at 120° C. to 130° C. for at least 2 hours to obtain a polysulfone hollow fiber membrane having an average pore size of 24 nm to 40 nm and a permeability coefficient of 7 or more. Therefore, even when the hollow fiber membrane was subjected to an immersion treatment by the production methods in Examples 1 and 2, a polysulfone hollow fiber membrane exhibiting both excellent separation performance and water permeability could be produced.

[0041] In Comparative Examples 1 and 2, the heating temperature in the immersion treatment was less than 120° C., so that the polysulfone hollow fiber membranes having the desired pore size were not obtained, and sufficient water permeability was not imparted to the polysulfone hollow fiber membranes, so that it was not possible to achieve both separation performance and water permeability in the polysulfone hollow fiber membranes.

[0042] In Comparative Example 3, the obtained polysulfone hollow fiber membrane had an average pore size of 24 nm or more and was excellent in separation performance, but the heating temperature in the immersion treatment was less than 2 hours, so the polysulfone hollow fiber membrane was not given sufficient water permeability, and therefore it was not possible to achieve both separation performance and water permeability in the polysulfone hollow fiber membrane.

[0043] In Comparative Example 4, the obtained polysulfone hollow fiber membrane had a permeability coefficient of 7 or more and was excellent in water permeability, but the heating temperature in the immersion treatment exceeded 130° C., so the average pore size was larger than 40 nm and the desired separation performance was not obtained. Therefore, it was not possible to achieve both separation performance and water permeability in the polysulfone hollow fiber membrane. [Explanation of symbols]

[0044] 10...resin head, 11...cylindrical container, 12...potting agent, 13...polysulfone hollow fiber membrane, 14...pressure gauge, 15...pipe, 16...supply pipe

Claims

1. A method for producing a polysulfone hollow fiber membrane, comprising discharging a spinning dope containing 10% by mass or more and 40% by mass or less of polysulfone, 1% by mass or more and 30% by mass or less of polyvinylpyrrolidone, and 1% by mass or more and 80% by mass or less of a water-soluble organic solvent together with a core liquid from a double ring nozzle, producing a hollow fiber membrane by dry-wet spinning, and then immersing the hollow fiber membrane in pressurized water at 120° C. or more and 130° C. or less for at least 2 hours.

2. The method for producing a polysulfone hollow fiber membrane according to claim 1, wherein the core liquid contains 30% by mass or more and 100% by mass or less of N,N-dimethylformamide.

3. The method for producing a polysulfone hollow fiber membrane according to claim 1 or 2, wherein the water-soluble organic solvent contains N,N-dimethylformamide.

4. 4. The method for producing a polysulfone hollow fiber membrane according to claim 1, wherein the average pore size of the polysulfone hollow fiber membrane after immersion is 24 nm or more and 40 nm or less.

Citation Information

Patent Citations

  • Treatment process for aromatic polysulfone porous membrane

    JP1990139022A

  • Method for imparting hydrophilic property to hollow fiber membrane of polysulfone

    JP1995155573A

  • Hollow fiber membrane for hemocatharsis, method for manufacturing the same, and blood purifier

    JP2003010322A

  • Hollow fiber membrane bundle and separation module

    JP2006130396A

  • Porous membrane, water purifier incorporating porous membrane and method for producing porous membrane

    JP2014073487A